2000
DOI: 10.1128/iai.68.4.2034-2042.2000
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Gene Expression in Innately Susceptible BALB/c Mice and Relatively Resistant C57BL/6 Mice during Infection with VirulentBurkholderia pseudomallei

Abstract: Production of cytokines including gamma interferon (IFN-␥) and tumor necrosis factor alpha (TNF-␣

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
140
1
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(151 citation statements)
references
References 53 publications
8
140
1
2
Order By: Relevance
“…Thus, our findings predict that pathological consequences of bacterial infections depend on the TNF-␣ allele expressed. It has indeed been shown that the two mouse strains we used respond in a different manner to bacterial infections (24,54). As a cytokine with a broad range of proinflammatory and immunostimulatory actions, TNF-␣ is thought to play a pivotal role in a number of human diseases including rheumatoid arthritis and periodontitis and a number of infectious and autoimmune diseases (55,56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our findings predict that pathological consequences of bacterial infections depend on the TNF-␣ allele expressed. It has indeed been shown that the two mouse strains we used respond in a different manner to bacterial infections (24,54). As a cytokine with a broad range of proinflammatory and immunostimulatory actions, TNF-␣ is thought to play a pivotal role in a number of human diseases including rheumatoid arthritis and periodontitis and a number of infectious and autoimmune diseases (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…BALB/c and C57BL/6 express different TNF-␣ alleles and differ in the response of their innate immune system (17)(18)(19)(20)(21)(22)(23)(24). In light of the pivotal role of TNF-␣ in mediating the osteoclastogenic effect of CpG-ODN, we studied the induction of osteoclastogenesis and TNF-␣ expression in cells derived from mouse strains expressing different alleles of the cytokine.…”
mentioning
confidence: 99%
“…PCR was performed as described using mouse gene-specific primers (18,19). The amplified DNA fragments were stained with ethidium bromide and photographed using Epi-Light UV FA1100 (Aisin Cosmos R&D Co., Japan).…”
Section: Methodsmentioning
confidence: 99%
“…This results in a cellular response that fails to control the infection and contributes to tissue damage and multiple organ failure [56]. In contrast, B6 mice develop a chronic infection that is associated with a moderate but transient induction of pro-inflammatory cytokines, allowing the temporary sequestration of Bp within phagocytes and induction of an adaptive immune response [56,60]. The heighted level of resistance exhibited in B6 mice is thought to have a genetic basis.…”
Section: Animal Modelsmentioning
confidence: 99%
“…The murine infection model has also been used to show both the importance of the host genetic background as well as host responses on the progression of a Bp infection [28]. BALB/c mice [57,58] and DBA/2J (D2) [55,59] mice are known to be extremely susceptible to the acute form of melioidosis, while C57BL/6 (B6) [28,55,56,58] mice exhibit a heightened level of resistance to the acute form of melioidosis, and tend to develop a chronic form of the disease. The acute melioidosis observed in BALB/c and D2 mice is characterized by significantly higher levels of pro-inflammatory cytokines, including a hyper-production of IFN-γ.…”
Section: Animal Modelsmentioning
confidence: 99%